Antibiotic Sensitivity Pattern in Neck Space infection (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Infection caused by microorganisms are common and may be serious and life threatening, requires immediate attention and management to get best outcome. The purpose of this study is to assess the anatomical spaces and causative microorganisms responsible for neck infections and evaluate the sensitivity pattern of the isolated microorganisms to antimicrobial agents.Materials and methods: This study was carried out in the Department of Otolaryngology- Head and Neck Surgery, Chittagong Medical College Hospital, from January to December 2018. A total of 70 cases were selected consecutively. All underwent surgical incision & drainage. Pus sample was obtained either by aspiration or by swab stick from the involved spaces and culture and sensitivity tests were performed.Results: The most common neck space infection were submandibular abscess 27 (38.57%) followed by Ludwig's angina 20 (28.57%). Out of 70 cases, 51(72.86%) cases yielded positive growth and 19(27.14%) cases showed no growth. Predominant microorganisms were Staphylococcus aureus, Streptococcuspyogenes, klebsiellaspecies and E coli. Staphylococcus aureus showed sensitivity to vancomycin, clindamycin, gentamycin. Streptococcus pyogenes showed sensitivity to cefuroxime, ceftriaxone and klebsiella species showed sensitivity to amikacin.Conclusion: Bacteriological examination and culture help to identify the causative microorganisms in neck abscess. It helps to isolate even the rarest of the organism and by knowing there sensitivity pattern, we can direct specific therapy against them. It thus helps in a more effective treatment and fast recovery of patients.Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 28-31